PERANCANGAN SISTEM INFORMASI PENGOLAHAN DATA SISWA BERBASIS WEB PADA BKB PAUD AL-BARKAH JERUK PURUT (Studi Kasus : BKB PAUD AL-Barkah Jeruk Purut, Kelurahan Cilandak Timur, Kecamatan Pasar Minggu, Jakarta Selatan) - Ilham Ramadhani, - (2021)
In the current condition, BKB PAUD Al-Barkah Jeruk Purut, in processing student data and other data such as employee data, financial data, spp payment data, and student activity data for 1 (one) period is done conventionally or recording with a ledger. By applying the conventional system in the BKB PAUD Al-Barkah will pose risks that can hinder the work of PAUD employees. The purpose of this research is to help design a web-based information system at BKB PAUD Al-Barkah Jeruk Purut to make it easier for employees to process student data, simplify student payment transaction processes, record student finances, and compile and display information on activities for 1 (one) period. The method used in this method uses the waterfall system development method which consists of 5 stages of the method, namely requirements, design, implementation, testing, deployment, and testing using BlackBox testing. This web-based information system is expected to help PAUD employees work more effectively in processing student data and can help students or guardians receive information on activities for 1 (one) period and student payments, and make it easier for students or guardians to make payment transactions without must come to BKB PAUD Al-Barkah Jeruk Purut.